THE GENDER PERSPECTIVE ON HUMAN TRAFFICKING IN INDONESIA - Lathifah, Ade; Noveria, Mita (Jurnal Masyarakat dan Budaya, 2014)
Human trafficking is commonly associated with women due to the fact that the majority of the victims are women. In reality, both men and women have been the victims of human trafficking through various exploitative and abusive treatments. This paper aims to describe human trafficking activities across the border areas in Indonesia based on the gender perspective. Several aspects of human trafficking are discussed, such as the pattern, the process and the impact of trafficking activities on the victim's life. Data and information for this article come from the reviews of several studies and scientific papers related to the human trafficking, particularly in Indonesia. This study shows that the males and females trafficked victims have different experience of abuse in a range of sectors, and therefore required different kind of support and protection. This paper aims to contribute in finding the solutions for the improvement of the existing human trafficking intervention. Keywords: human trafficking, gender perspective, Indonesia